Variable tellurite resistance profiles of clinically-relevant Shiga toxin-producing Escherichia coli (STEC) influence their recovery from foodstuffs. (October 2016) - Kerangart, Stéphane; Douëllou, Thomas; Delannoy, Sabine; Fach, Patrick; Beutin, Lothar; Sergentet-Thévenot, Delphine; Cournoyer, Benoit; Loukiadis, Estelle
Abstract: Tellurite (Tel)-amended selective media and resistance (Tel-R) are widely used for detecting Shiga toxin-producing Escherichia coli (STEC) from foodstuffs. Tel-R of 81 O157 and non-O157 STEC strains isolated from animal, food and human was thus investigated. Variations of STEC tellurite minimal inhibitory concentration (MIC) values have been observed and suggest a multifactorial and variable tellurite resistome between strains. Some clinically-relevant STEC were found highly susceptible and could not be recovered using a tellurite-based detection scheme. The ter operon was highly prevalent among highly Tel-R STEC but was not always detected among intermediately-resistant strains. Many STEC serogroup strains were found to harbor sublines showing a gradient of MIC values. These Tel-R sublines showed statistically significant log negative correlations with increasing tellurite concentration. Whatever the tellurite concentration, the highest number of resistant sublines was observed for STEC belonging to the O26 serogroup. Variations in the number of these Tel-R sublines could explain the poor recovery of some STEC serogroups on tellurite-amended media especially from food products with low levels of contamination. Comparison of tellurite MIC values and distribution of virulence-related genes showed Tel-R and virulence to be related. Highlights: Tellurite MICs of O157 and non-O157 STEC vary, the lowest reaching 0.5 μg/mL. STEC Tel-R may involves complex mechanisms not only dependent upon the ter locus. Observed Tel-R sublines are correlated with serogroup and tellurite concentration. Susceptible STEC would be missed using commercial tellurite-based selective media. STEC Tel-R may affect their recovery in foodstuff contaminated with less than 4 cfu/g.